2013
DOI: 10.1245/s10434-013-3184-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased BCAR1 Predicts Poor Outcomes of Non-small Cell Lung Cancer in Multiple-Center Patients

Abstract: Objective We aimed to study the prognostic value of BCAR1 expression and its associations with clinical-demographical characteristics in multiple centers of non-small cell lung cancer (NSCLC) patients. Methods Gene expression microarray (mRNA) of 77 adenocarcinomas from Mayo Clinic, RNA-sequencing of 508 NSCLC from The Cancer Genome Atlas (TCGA), and immunohistochemistry(IHC) stain of BCAR1-protein expression in 150 cases from Daping Hospital were included in the study. The association of mRNA or protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Deng et al found that miR-1247 was downregulated in lung squamous cell carcinoma tissue samples compared with normal tissues by a chip detection assay 14. Moreover, a functional role of miR-1247 has been found in a number of cancers, including prostate cancer,12 osteoblasts from osteosarcoma,11 and pancreatic cancer 28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deng et al found that miR-1247 was downregulated in lung squamous cell carcinoma tissue samples compared with normal tissues by a chip detection assay 14. Moreover, a functional role of miR-1247 has been found in a number of cancers, including prostate cancer,12 osteoblasts from osteosarcoma,11 and pancreatic cancer 28.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of miR-1247 has been found to be decreased in osteosarcoma cancer stem cells and influences human osteosarcoma oncogenesis by the regulation of MAP3K9 11. Furthermore, miR-1247 was found to be downregulated in lung adenocarcinoma and squamous carcinoma cancer tissue compared with normal tissues 14. Yet the function and mechanism of miR-1247 in NSCLC has rarely been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low RRM1 expression tend to have OS only less than 4 months longer in comparison to patients with high expression of the molecule (74). High expression of BCAR1 is a slightly more powerful prognostic factor of OS in NSCLC, as the HR in this case is ~2.5 (75). This data indicates that the novel markers are more powerful in predicting the course of LC.…”
Section: Discussionmentioning
confidence: 72%
“…p130Cas is also reported to be involved in the development and progression of several human cancers, including breast cancer [19,20], prostate cancer [21,22], as well as lung cancer [23]. In lung cancer, BCAR1 was usually overexpressed, and increased BCAR1 predicts poorer prognosis in non-small lung cancer [23,24]. In this report, the detected BCAR1 variant occurred an 11 bp insertion at codon 314 which locates at the substrate binding domain, indicating that its association with effectors proteins would be impaired in some extent, thus leading to a wide-range downstream consequence.…”
Section: Discussionmentioning
confidence: 99%